2018
DOI: 10.3389/fphar.2018.00495
|View full text |Cite
|
Sign up to set email alerts
|

The Somatostatin Receptor-4 Agonist J-2156 Alleviates Mechanical Hypersensitivity in a Rat Model of Breast Cancer Induced Bone Pain

Abstract: In the majority of patients with breast cancer in the advanced stages, skeletal metastases are common, which may cause excruciating pain. Currently available drug treatments for relief of breast cancer-induced bone pain (BCIBP) include non-steroidal anti-inflammatory drugs and strong opioid analgesics along with inhibitors of osteoclast activity such as bisphosphonates and monoclonal antibodies such as denosumab. However, these medications often lack efficacy and/or they may produce serious dose-limiting side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 147 publications
9
33
1
Order By: Relevance
“…Using μCT scans, histological assessment with H&E staining, and immunohistochemical staining against Cytokeratin 18 in tibial bones, we have demonstrated that cancer cells were present in the bones and pathological changes associated with metastatic lesions such as osteolytic bone degradation was evident. This was the case both during the period when pain behaviour (< day 21) was evident and also during the period when pain behaviour was apparently resolved (> day 21), as reported in detail in our previous studies . Group of rats inoculated with live W256 cells developed significant ( P ≤ .05) mechanical hypersensitivities in the bilateral hindpaws at days 7–10 post‐inoculation (pain behaviours present), when compared to group of rats inoculated with HK W256 cells (Figure ).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Using μCT scans, histological assessment with H&E staining, and immunohistochemical staining against Cytokeratin 18 in tibial bones, we have demonstrated that cancer cells were present in the bones and pathological changes associated with metastatic lesions such as osteolytic bone degradation was evident. This was the case both during the period when pain behaviour (< day 21) was evident and also during the period when pain behaviour was apparently resolved (> day 21), as reported in detail in our previous studies . Group of rats inoculated with live W256 cells developed significant ( P ≤ .05) mechanical hypersensitivities in the bilateral hindpaws at days 7–10 post‐inoculation (pain behaviours present), when compared to group of rats inoculated with HK W256 cells (Figure ).…”
Section: Resultssupporting
confidence: 81%
“…It is necessary that we understand the gene level changes occurring in the neural tissues that underpin the pathophysiology of pain in the preclinical models used in the drug discovery processes. Previous works from our laboratory have established that the Walker 256 breast cancer cell‐induced bone pain model in rats is a research tool that mimics key features of the human BCIBP condition and can be very useful in investigating the mechanisms of BCIBP and in discovery of novel analgesics against this debilitating pain condition . However, there is insufficient information on global gene expression changes at the level of dorsal root ganglia (DRGs) and the spinal cord, occurring in the pathophysiology of BCIBP.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of SST 4 in the central nervous system leads to M-current augmentation and epileptiform activity inhibition in hippocampal CA1 pyramidal cells [ 10 ]. In addition, SST 4 activation increases potassium conductance via GIRK channels leading to consequent suppression of voltage-sensitive calcium channels in primary sensory neurons of the dorsal root ganglia (DRG) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This highlights an unmet medical need for the discovery of efficacious and well‐tolerated novel analgesic agents. Hence, we assessed the SST 4 receptor agonist, J‐2156, 14 in our LBP‐5X rat model to determine its potential as a novel pharmacotherapeutic treatment for cLBP.…”
Section: Discussionmentioning
confidence: 99%
“…This unmet medical need is driving research aimed at discovery of new molecules that are efficacious and well‐tolerated. Of interest, J‐2156, an investigational small molecule somatostatin type 4 (SST4) receptor agonist has been shown by our laboratory to alleviate prostate cancer‐induced bone pain in rats 14 as well as chronic mechanical LBP in a moderately severe (LBP‐10X) rat model 15 . However, its efficacy in a mild to moderate rat model of chronic mechanical LBP remains to be assessed.…”
Section: Introductionmentioning
confidence: 99%